Removal of Lead (II) from aqueous solutions using Fe3O4-MWCNTs - Zehoua Rehimia. . . .; Halladja Sabrina; Ayadi Hassan; Issam Boudraa; Sevede ustun; Hanife Büyükgüngör (University Of Eloued جامعة الوادي, 2020)
In the present work, a magnetic nanocomposite (Fe3O4/MWCNTs: 2/1) was prepared from multi-walled carbon nanotubes and magnetite using coprecipitation method. The sample was characterized by X-ray diffraction (XRD) and observed with scanning electron microscopy (SEM) analysis. The removal of lead ions was investigated using the adsorption process onto (Fe3O4/MWCNTs: 2/1). The effect of important parameters was studied: initial pH, initial concentration of heavy metal and temperature. As a result, the optimum adsorption conditions were estimated to be about 5, 80 mg.L-1 and 30 ºC, respectively. Langmuir isotherm best suited the adsorption of lead (II) onto composite. Thermodynamic study suggests that the adsorption process was favorable and exothermic. This adsorbent exhibited an efficient adsorption capacity (50 mg.g-1) and simple separation .
2/1 adsorbent
Intervention
Keywords: Carbon nanotubes; magnetite; adsorption; lead; isotherm